Analisis Efektivitas dan Kontribusi Penerimaan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan Terhadap Pendapatan Asli Daerah Kota Yogyakarta - Ronowati Tjandra; Nanda Putri Febriyanti (Jurnal Akuntansi dan Pajak, 2026)
This research aims to analyze the effectiveness and contribution of Rural and Urban Land and Building Tax revenues to the Original Regional Revenue of Yogyakarta City in 2020-2024. The population of this study is the Yogyakarta City Government's PAD Realization Report and the PBB Realization Report. The sample of this study is the Yogyakarta City Government's PAD Realization Report for 2020-2024 and the PBB-P2 Realization Report for 2020-2024. The sampling technique applied is non-probability sampling or non-random sampling, which uses a purposive sampling approach. The results of the analysis show that the effectiveness of PBB-P2 revenues in Yogyakarta City during the period 2020 to 2024 is classified as very effective. Although the level of revenue effectiveness is relatively high, the contribution of PBB-P2 to the Original Regional Revenue of Yogyakarta City during the period 2020 to 2024 is still in the low category, with an average contribution of 14.62%. Many factors influence the low contribution of PBB-P2 to the Original Regional Revenue of Yogyakarta City in 2020-2024.